Knowledge and awareness of Hepatitis B and its associated factors among students of medical faculties at the International Islamic University Malaysia’s Kuantan campus - Ibrahim, Wisam Nabeel; Mazlan, Ain Nadiah; Al-Mahmood, Sinan; Othman, Noratikah (IIUM Press, 2018)
Objective: this study aims to assess the knowledge and awareness of hepatitis B and its associated factors among students of medical colleges at Kuantan Campus, the International Islamic University Malaysia. Methods: A cross-sectional study design was used, and data collection was carried out using a self-structured close-ended questionnaire. Descriptive and analytic statistics were performed with independent t-test, One Way ANOVA and a correlation analysis determine any significant differences between the groups with p < 0.05 significance value Results: According to the results, there was a significant (p < 0.001) association between the type of Faculty with knowledge and awareness about hepatitis B. In addition, the results showed an association between year of study with the knowledge and awareness of hepatitis B (p < 0.001). Furthermore, there was an association between duration of clinical experience with knowledge and awareness of hepatitis B (p < 0.001). The results showed that there was no association between gender with knowledge and awareness of hepatitis B (p > 0.05). Conclusion: levels of knowledge showed a strong correlation with levels of awareness, meaning that students with high knowledge also had